1978
DOI: 10.1007/bf00007994
|View full text |Cite
|
Sign up to set email alerts
|

A partial analysis of ecological segregation in the chironomid community of a bog lake

Abstract: A small dystrophic lake was found to support 19 species of chironomid larvae, 13 of which are relatively abundant while the other six are classified as rare as they collectively constituted less than 0.25% of the total chironomid community. With the exception of one species pair, evidence of ecological segregation could be demonstrated for all abundant species that could be morphologically distinguished as larvae . Both members of the overlapping pair fed mainly upon coarse detritus, the most abundant food res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…Cell displacement would alter competitive interactions of the remaining cells, and the displaced cells would probably fall into areas less suitable for growth . Contrary to Ramcharan & Paterson's (1978) report of only detrital material in C. scutellata guts, larvae from Nonquit Pond had diatom frustules and algal fragments in their guts . Direct observation of feeding larvae showed them to consume attached, living diatom cells .…”
Section: Resultscontrasting
confidence: 47%
“…Cell displacement would alter competitive interactions of the remaining cells, and the displaced cells would probably fall into areas less suitable for growth . Contrary to Ramcharan & Paterson's (1978) report of only detrital material in C. scutellata guts, larvae from Nonquit Pond had diatom frustules and algal fragments in their guts . Direct observation of feeding larvae showed them to consume attached, living diatom cells .…”
Section: Resultscontrasting
confidence: 47%
“…None was found and, if present, it was below the sensitivity of the methods. Ramcharan & Paterson (1978) provided an estimate of the annual biomass production of the leaves and stems of Nuphar variegatum, the only common macrophyte in the lake. An estimate of rhizome standing stock biomass was made by determining, through probing, the spatial distribution of rhizomes along a transect.…”
Section: Autochthonous Inputsmentioning
confidence: 99%
“…Also it was hoped to be possible to comment on the relative importance and role of allochthonous inputs, versus autochthonous production, on the structure and biological functioning of such a brown water, acid lake. Ramcharan & Paterson (1978) have previously described the study site. It is located 1.75 km S.W.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on invertebrates living in macrophyte stands have shown a great species richness and a high density of organisms when compared with the benthic fauna in sediments (Soszka, 1975;Ramcharan & Paterson, 1978). Vicent et al (1982) observed that the fauna in the macrophytes presents a magnitude of two to three times the abundance of zoobenthos in the litoral zone.…”
Section: Introductionmentioning
confidence: 99%